Investigation of the wind power potential of the Hernád valley - Tar, Károly; Kircsi, Andrea; Szegedi, Sándor; Tóth, Tamás; Vass, Róbert; Kapocska, László (Acta Geographica Debrecina Landscape & Environment series, 2011)
The University of Debrecen, Department of Meteorology has carried out research into the climatic and social-economic conditions of the Hernád valley in the scope of a scientific project (OTKA K 75794) between 2009 and 2012. The aim is to find out the optimal area for wind and solar energy, as well as biomass utilization. Our purpose is to work out a model wherein the complex evaluation of natural and social-economic conditions and effects can eventually result in a sustainable and conflictfree land use. The results of the research will be useful in working out a regional improvement based on the use of renewable energy sources to help the local decision-making process.